Empowerment of Government Public Relations Office Post Restructuring ( Case Study on Informatics and Public Relations Office of Jakarta City Administration) - Tria Patrianti (KOM & REALITAS SOSIAL, 2011)
This research aims to seek better understanding on the empowerment of the public relations office following the restructuring conducted by Jakarta City Administration.Â Involving 11 respondents, the research utilizes qualitative research method with case study approach.The background issues in the research are as followed: (1) Why the role and function of public relations office at Jakarta Administration remain insignificant regardless of the restructuring; (2) What the public relations officeâs role and function are in the attempts to empower public relations following the restructuring; and (3) What the ideal pattern of the empowerment of government public relations office at Jakarta City Administration is. The research shows that (1) The restructuring has been quite efficient, but the public relations office has yet to be effective in promoting Governorâs policies; (2) Following the restructuring, the public relations office has yet to be empowered optimally and is consdered weak in carrying out its tasks and function.Â The weakness was attributed to, first, the complicated problems and organizational structure at the Administration, as well as the ego of different institutions.Â Second, Â the slow service in providing public information due to the low pace of coordination between offices.Â Public relations officers do not have the full authority to dictate the Governor related to this public image.Â Third, public reltions is still positioned as technical support, instead of managerial or strategic position; (3) The Governor has high commitment in supporting public relationsâs function.Â It is up to the public relations office itself to implement it well; (4) The quality of human resourcs is subject to improvement through training or education ; (5) Public relations budget is still modest; and (6) The infrastructure to provide public information are readily available, suc as news website, hotline service and social media.